Influence of Fertilizer Levels on the Growth and Yield of Black Cumin (Nigella sativa L.) (The Agriculturists, 2016)
An experiment was conducted at the research farm of Crop Physiology and Ecology Department, Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh, during November 2013 to April 2014 to determine the growth and yield performance of four varieties of black cumin (Exotic variety, BARI kalozira-1, Faridpur local and Natore local) as influenced by three levels of fertilizers (40-20-30 Kg ha-1, 80-30-45 Kg ha-1 and 120-40-60 Kg ha-1 N-P-K, respectively).  The experiment was conducted in a randomized complete block design (RCBD) with three replications. First flower bud initiation day, capsule setting, and capsule ripening in 50% plant were not significantly influenced by N-P-K fertilizer levels. The secondary branch plant-1, tertiary branch plant-1,plant height at harvest, capsule length, capsule diameter and 1000 seed weight of black cumin were also not influenced significantly by the fertilizer levels. The dry matter weight  plant-1, primary branch plant-1, fruit plant-1, seed capsule-1 and grain yield of black cumin genotypes were significantly influenced by different levels of N-P-K fertilizers. Natore local gave maximum dry matter  production plant-1  at 55 DAS with moderate  N-P-K levels and at 70 DAS with higher N-P-K fertilizer levels (0.22 and 1.06 g, respectively), whereas Exotic black cumin genotype showed maximum dry matter plant-1  at 85 and 100 DAS with higher N-P-K fertilizer levels  (2.30 and 4.97 g, respectively). Exotic variety produced maximum grain yield (3.43 g plant-1 and 2.30 t ha-1)  at higher level of N-P-K fertilizer, but BARI kalozira-1 (2.95 g plant-1  and 1.95 t ha-1), Faridpur local (2.80g plant-1  and 1.90 t ha-1) and Natore local (2.69 g plant-1  and 1.80 t ha-1) showed maximum yields at moderate N-P-K fertilizer levels. Among the test varieties of black cumin, the exotic variety showed better yield performance than the others.The Agriculturists 2015; 13(2) 97-104